The 'fishnet approach' to livelihood improvement in depressed basins: evidence from BRAC's Integrated Development Programme. Issue 4 (18th May 2020) - Ara, Jinnat; Shahed, Syeda Sitwat; Rahman, Rehnuma; Ahmad, Sibbir; Das, Narayan Chandra
ABSTRACT: The multidimensional nature of poverty renders comprehensive development efforts encompassing livelihoods, health, and education as well as communal support, essential for achieving equality in growth. Such an integrated service approach has neither been widely practiced nor assessed: therefore, this article analyses the impact of BRAC's Integrated Development Programme implemented in remote depressed basins in north-eastern Bangladesh. Households within the intervened area are not only economically better off due to higher purchasing power, insurance against crisis as well as occupational diversity, but also have stronger social cohesion, especially women.